1960
DOI: 10.1021/j100832a014
|View full text |Cite
|
Sign up to set email alerts
|

VAPOR PRESSURE OF THORIUM1

Abstract: The vapor pressure of solid thorium was determined over the temperature interval 1757 to 1956°K. by the vacuum evaporation method of Langmuir. Special purification of the thorium was necessary since traces of Th02 react with thorium to give ThO(g). Thorium also reacts with residual gaseous oxygen in the vacuum system to form ThO(g). The latter effect was found to be negligible at residual oxygen pressures of less than 2 X 10 ~* mm. The vapor pressure equation for Th(s) -Th(g) is log Patm = -28,780 =fc 620/7' .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1964
1964
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…According to Mclntyre and Janz 4 , the carriers of electric current in a HgI2-HgBr2 mixture should be considered to be the Hgl + , Hgl3, HgBr + and HgBr3 ions. With this assumption and using the significant structure theory of liquids proposed by Eyring et al 15 , Mu Shik Jhon et al 16 have calculated some physical properties of mercury halides in good agreement with experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Mclntyre and Janz 4 , the carriers of electric current in a HgI2-HgBr2 mixture should be considered to be the Hgl + , Hgl3, HgBr + and HgBr3 ions. With this assumption and using the significant structure theory of liquids proposed by Eyring et al 15 , Mu Shik Jhon et al 16 have calculated some physical properties of mercury halides in good agreement with experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Grantham and Yosim 2 have shown that the negative temperature coefficient of electric conductivity in the melts is a consequence of the decrease in density and increase in covalent character of the melt as the temperature increases. Such an explanation is satisfactory in view of the work of Darnell and McCollum 4 , who achieved a large increase in ionicity of molten Hgl2 by subjecting it to a high pressure.…”
Section: Introductionmentioning
confidence: 93%
“…UO(g) has been found to be the most important species in equilibrium with a mixture of U(l) and U02(s),37 just as Th(s) containing dissolved 0 produces large amounts of ThO(g). 38 No detailed theoretical explanation of such behavior has yet been made. However, it is likely that other gaseous carbide and oxide complexes will soon be identified and that species ratios as a function of stoichiometry will be better explored.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of O2 in the upper + chamber enhances the intensity rh0 2 + peak and dec-eases the intensity of Th Figure 6C. When the electron beam is turned off, all peaks disappear with the exception of ThcT which proves that this ion is formed directly through a chemiionization process such as shown by equation reaction (3 «•»'""»■»"i-w™BnwP^«ppwiWTOW|WWPö*w*"T'w»PPiw^^ Further mass spectrometric and spectroscopic work is now in progress.…”
mentioning
confidence: 86%